The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/s1677-5538.ibju.2015.0135
|View full text |Cite
|
Sign up to set email alerts
|

Can intraurethral stimulation inhibit micturition reflex in normal female rats?

Abstract: Objective The study was designed to determine the effect of low frequency (2.5Hz) intraurethral electrical stimulation on bladder capacity and maximum voiding pressures.Materials and Methods The experiments were conducted in 15 virgin female Sprague-Dawley rats (220–250g). The animals were anesthetized by intraperitoneal injection of urethane (1.5g/kg). Animal care and experimental procedures were reviewed and approved by the Institutional Animal Care and Use Committee of Antwerp University (code: 2013-50). Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Regarding the clitoris, we observed sensory innervation from L7 and S1 SG, input from S1 sympathetic trunk ganglia, direct inputs from intermediolateral regions of L7‐S1 spinal cord segments, a very small contingent from the caudal mesenteric ganglia, but no input from pelvic plexus ganglia in mesenteries collected near the bladder wall and ureter. In rats, electrophysiological methods show that both pudendal and hypogastric nerves carry afferents from the clitoris (Yu et al, ). Similarly, we previously observed that nerves to the clitoris branched only from pudendal nerves (Gomez‐Amaya et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the clitoris, we observed sensory innervation from L7 and S1 SG, input from S1 sympathetic trunk ganglia, direct inputs from intermediolateral regions of L7‐S1 spinal cord segments, a very small contingent from the caudal mesenteric ganglia, but no input from pelvic plexus ganglia in mesenteries collected near the bladder wall and ureter. In rats, electrophysiological methods show that both pudendal and hypogastric nerves carry afferents from the clitoris (Yu et al, ). Similarly, we previously observed that nerves to the clitoris branched only from pudendal nerves (Gomez‐Amaya et al, ).…”
Section: Discussionmentioning
confidence: 99%